The Effect of Financial Performance on the Stock Return of Consumer Goods Sector Companies - Nurpadila (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This type of research is called comparative causal research. The population of this study is consumer goods companies for the period 2016-2020. Samples were taken using a purposive sampling technique. The sample consisted of 6 companies from 16 consumer goods companies listed on the Indonesia Stock Exchange in 2017-2020 so the research data analyzed amounted to 30. The data collection method used was documentation. The data analysis techniques used are descriptive statistics, classical assumption tests, and multiple linear regression analysis. Based on hypothesis testing using the t-test, it is concluded that the current ratio has a positive but not significant effect on stock return, the return on assets has a negative and insignificant effect on stock return, and the debt-to-equity ratio has a negative and insignificant effect on stock return.